Herz & Gesundheit - Mayer-Berger W (Dynamic Media Sales Verlag, 2018)
Endurance training is the mainstay in the exercise and sports therapy of cardiovascular patients. Both morbidity and mortality are improved in the long-term. The importance of this therapy is still underestimated, and it seems prudent to give individualized training recommendations on mode, duration and intensity of physical activity, analogous to prescription of medication. The level of fitness being low in especially cardiovascular patients, the aim should be to start with a rather low intensity and duration (begin low, go slow) with clear instructions for increasing the exertion. At least a moderate level of physical activity should be achieved, if possible and wished even a higher intensity. A moderate intensity (150min per week at 3 to 6 metabolic equivalents MET or 50 to 100 Watt with 70kg body weight, desirable at least 1500kcal per week of energy consumption) should be reached. More recent data indicate that in endurance training, approximately 80% of the maximum heart rate achieved in the exercise test, possibly even 5% more, can be recommended (if there are no symptoms!). Alternative training modes such as, for example, high intensity interval training, have not yet proved better neither in coronary heart disease nor in heart failure. Patients with heart failure should have a cardiopulmonary exercise test in order to determine the appropriate level of exercise based on the first ventilatory threshold. KEY WORDS: Endurance Training, Exercise, Cardiovascular Patients, Exercise Intensity, High Intensity Interval Training